2004
DOI: 10.1128/jb.186.13.4085-4099.2004
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-Based Analysis of theStaphylococcus aureusσBRegulon

Abstract: Microarray-based analysis of the transcriptional profiles of the genetically distinct Staphylococcus aureus strains COL, GP268, and Newman indicate that a total of 251 open reading frames (ORFs) are influenced by B activity. While B was found to positively control 198 genes by a factor of >2 in at least two of the three genetic lineages analyzed, 53 ORFs were repressed in the presence of B . Gene products that were found to be influenced by B are putatively involved in all manner of cellular processes, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
382
3
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 361 publications
(421 citation statements)
references
References 88 publications
33
382
3
1
Order By: Relevance
“…In addition to mgrA and agr, recent reports showed that sae and sigB were also involved in capsule regulation (Steinhuber et al, 2003;Bischoff et al, 2004). Taken together, these results indicate that capsule is under the regulation of a surprisingly large number of regulators.…”
Section: Discussionsupporting
confidence: 54%
“…In addition to mgrA and agr, recent reports showed that sae and sigB were also involved in capsule regulation (Steinhuber et al, 2003;Bischoff et al, 2004). Taken together, these results indicate that capsule is under the regulation of a surprisingly large number of regulators.…”
Section: Discussionsupporting
confidence: 54%
“…3 In addition, a microarray study suggests a σ B -dependent regulation of SA2104 and the presence of a σ B -dependent promoter located downstream of RsaOG. 8 These observations strongly support that SA2104 is transcribed independently of rsaOG.…”
Section: Race Mapping Was Performed As Insupporting
confidence: 68%
“…The deletion of the msaABCR operon alters the expression of several global regulators, including sarA, agr and sigB, all of which have been shown to be indirectly involved in capsule production (Bischoff et al, 2004;Pané-Farré et al, 2006;Meier et al, 2007;Dassy et al, 1993;Sahukhal & Elasri, 2014). The regulatory mechanism for msaABCR has not yet been defined.…”
Section: Introductionmentioning
confidence: 99%